Determinan Carbon Emission Disclosure Dengan Peringkat Proper Sebagai Variabel Mediasi Pada Perusahaan Non Keuangan Di Indonesia Tahun 2015-2019 - Retnosari Widiastutik; Muhammad Khafid (Universitas Katolik Soegijapranata Semarang, 2021)
Prior studies on carbon emission disclosure have found conflicting results regarding the role of firm size, leverage, and financial performance in explaining carbon emission disclosure. This study attempts to probe the issue by introducing PROPER rating as mediating variable. Specifically, this study examines the role of PROPER rating in moderating the effect of firm size, financial performance, and leverage on carbon emission disclosure. Sample was selected from IDX for period of 2015-2019. As much as 150 firm observations were available for test of hypothesis. Using mediating regression analysis, results showed that company size is associated with PROPER rating. Leverage and financial performance have no effect on PROPER rating. In addition, while company size and leverage variable are associated with carbon emission disclosure, financial performs has no effect on carbon emission disclosure. PROPER rating can mediate the relationship between company size and carbon emission disclosure.